POINT COORDINATION MECHANISM BASED MOBILE AD HOC NETWORK INVESTIGATION AGAINST JAMMERS - Nourildean S.W.; Jasim S.I.; Abdulhadi M.T.; Jaber M.M. (Technology Center, 2023)
In this paper, a jamming attack (a kind of Denial-of-Service attack) was investigated, which interfered with the normal operation of a Mobile Ad Hoc network, which is more vulnerable to various attacks because of its self-configuration, dynamic characteristics, therefore, jammers would affect the network QoS parameters by reducing the throughput and increasing the delay. This problem is solved in this study by enabling the Point Coordination Function, which is a media access mechanism specified by the IEEE standard in some selected MANET nodes (guard nodes) to improve the deficiency of MANETs performance. The Riverbed modeler was utilized as a simulation tool. In this study, six jammers with two different transmission power values had been applied. In a number of different simulation scenarios with and without jammers, the estimated results showed that the jammers affected the network performance by increasing the delay to 3.0658 sec and decreasing the throughput to 120200.59 bits/sec. After enabling the PCF mechanism in a number of selected nodes, the results allowed the user to solve the problem by improving the network deficiency so that the throughput had been increased to 137478.32 bits/sec and the delay had been decreased to 0.7556 sec. It can be concluded that PCF is a good improvement for different levels of jammer transmission power such as 0.01 W and 0.001 W, and PCF also improved the networks delay and throughput when the number of PCF enabled nodes had been increased to 10 nodes and 12 nodes, respectively. The improvement is also increased. This study can be used in practice for any ad hoc network when attacked by jammers 2022, Authors. This is an open access article under the Creative Commons CC BY license